Analisis Gerak Teknik Dasar Hit dan Reverse Hit Terhadap Kecepatan Bola dan Ketepatan Sasaran - hari purnomo (Jendela Olahraga, 2019)
ABSTRACTThe purpose of this study was to analyze movement in doing basic technics, hit and reverse hit, on hockey field. There was seven aspects to be analyzed such as ball’s velocity, accuration, the angle of right arm (hit) / left arm (reverse hit), the angle of right and left leg, and the distance of leg. With these result, hopefully can be used as refferences in the practice, specifically on basic technics, hit and reverse hit. Data took from 6 man national hockey athletes (professional) and 6 man Surabaya hockey athletes (beginner). The test had done on each athletes did hit and reverse hit on 5 times that recorded used Handycam Sony HDR CX 450 then being analyzed used Software Dartfish Teampro 5.5. According to the analyze that used p level significant (0,05) that showed the significant difference from hit technic to the ball’s velocity from national hockey athletes (professional) is 19,22 m/s. It is better than Surabaya hockey athletes (beginer) with the ball’s velocity average is 12,55 m/s. The result also showed that there is significant difference to reverse hit technic with the ball’s velocity average is 18,07 m/s from national hockey athletes (professional). This result is better than from Surabaya hockey athletes (beginner) with the ball’s velocity average is 14,17 m/s. However, on the accuration, the result showed that there is no significant difference from both of the groups. In short, according to the result, the coach should more be focused to watch the angle of arm to the touch phase, the angle of right leg on the first phase to the next phase, the angle of left leg on the first phase, and the distance of leg on the first phase up to the next phase in doing basic technic; hit. Meanwhile, to do basic technic; reverse hit, the coach should more be focused to the angle of arm on the first phase and touch face, the angle of right leg on the touch phase and the next phase, and the angle of left leg on the first phase to the next phase.Keywords : accuration, ball’s velocity, reverse hit, hit, movement analyze.